A study of antimicrobial effect of Lactiplantibacillus plantarum 8P-A3 supernatant on nosocomial isolates of Klebsiella pneumoniae and Acinetobacter baumannii - Belova I.V.; Shirokova I.Yu.; Tochilina A.G.; Kovalishena O.V.; Belyanina N.A.; Tulupov A.A.; Molodtsova S.B.; Seliverstov A.N.; Kropotov V.S.; Solovyova I.V. (Клиническая микробиология и антимикробная химиотерапия)
Objective.